Enhancing SME Competitiveness Through the Implementation of Strategic Management Based on Local Business Innovation - Muhamad Imam Syairozi; Luluk Nur Azizah (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The background of this research is based on the importance of enhancing SME competitiveness amidst global competition and digital disruption, which requires effective managerial strategies and innovative approaches rooted in local potential. The purpose of this study is to investigate the impact of local business innovation and strategic management on SMEs' competitiveness, with innovation performance serving as a mediating variable. This research employs a quantitative explanatory approach with the Partial Least Squares-Structural Equation Modeling (PLS-SEM) analysis technique. The respondents consisted of 100 SME actors selected using purposive sampling. The data collection instrument used was a questionnaire. The results indicate that strategic management has no direct effect on SME competitiveness but does significantly affect innovation performance. Conversely, local business innovation has a direct and significant impact on both SME competitiveness and innovation performance. Innovation performance is found to have the most decisive influence on SME competitiveness and mediates the relationship between strategic management and local business innovation in terms of competitiveness. These findings emphasize that enhancing SME competitiveness heavily depends on the success of innovations developed through strategic planning and leveraging local strengths. This study contributes to the literature on SME strategies and serves as a practical reference for business actors in formulating innovation policy directions.